Deep Learning Architectures: A Review of Convolutional, Recurrent, and Transformer Models - Kalyani Ashok Bedekar, (AG Volumes, 2025)
Deep learning structures have greatly revolutionized artificial intelligence by offering advanced pattern recognition and automatic features learning using large and complex data. This review includes the complex analysis of three of the most significant deep learning architectures that are Convolutional Neural Networks (CNNs), Recurrent Neural Networks (RNNs), and Transformer models. CNNs are very efficient in image processing whereas RNNs and their variants e.g. LSTM and GRU are efficient to model sequential and time-varying data. Transformer models, which are driven by the self-attention mechanisms, have transformed the natural language processing and have found their use in the vision and multimodal learning. The review is a synthesis of the recent literature which emphasizes architectural improvements, hybridization, optimization techniques, and domain-specific applications such as healthcare, remote sensing, cybersecurity, genomics and IoT. Even though they perform exceptionally, there are research issues like computational complexity, interpretability, and data dependency, as well as resource demands, that are still of critical importance. The paper offers an understanding of modern trends and the future of deep learning designs.